The association between mode of delivery at birth and wheezing trajectories - Evidence from the UK Millennium Cohort Study - Alterman, N; Kurinczuk, J; Quigley, M (BMJ Publishing Group, 2018)
Delivery by caesarean section has been identified as a risk factor for asthma. Meta-analyses have reported a 20% increased risk for childhood asthma or its common symptom – wheezing. However, asthma is a heterogeneous disease with distinct phenotypes portrayed as various wheezing trajectories. We sought to assess the relationship between mode of delivery at birth and three commonly identified wheezing trajectories of childhood, as well as additional asthma-related outcomes.